Technological Aspects of Preservation and Processing of Edible Shell Fishes V. Cold Storage Changes in Mussels (Mytilus edulis) and Clams( Villortia Sp.) - George, Chinnamma (Fishery Technology, 1974)
The changes in chemical, bacteriological and organoleptic qualities of mussels and clams during freezing and subsequent frozen storage have been studied in relation to the holding time in ice prior to freezing and the shelf-life of the product is determined.